(untitled) (Texas Journal of Medical Science, 2022)
Water is a structural component of all cells and tissues. It binds to a number of biologically active polymers, in particular, glycogen (one gram of glycogen holds 1.5 ml of water); proteins whose molecules are surrounded by a solvate shell; glycosaminoglycans, resulting in the formation of a special gel-like state of the main intercellular substance, structured at the molecular level. Metabolic processes occurring in cells require a constant supply of nutrients to them. Their movements are carried out together with water, which is a universal solvent of organic and inorganic compounds. Together with water, metabolic products formed in the cells are transported and excreted from the body. Water is an essential component of many metabolic reactions: hydrolysis, oxidation, hydration, etc.; it is involved in the implementation of anabolic and catabolic processes and maintaining body temperature. Water is directly involved in the regulation of the body’s heat balance (preservation, distribution and release of heat). One of the most important properties of a living organism is movement in space. This function in humans is performed by the musculoskeletal system (ODA), which consists of two parts: passive and active. The first includes bones that connect to each other in various ways, the second - muscles. The bones of the skeleton are levers driven by muscles. As a result of this, body parts change position relative to each other and move the body in space. Bones and joints participate passively in movement, obeying the action of muscles, but play a leading role in the implementation of the supporting function. A certain shape and structure of the bones give them great strength, the reserve of which for compression, stretching, bending significantly exceeds the loads that are possible during the daily work of the musculoskeletal system. The ligaments and cartilages of the joints also have a large margin of safety